Genetic Testing in Huntington's Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The historical and clinical profiles of Huntington's disease (HD) presenting in 44 juveniles who were tested for CAG repeat expansions in the gene for HD were defined in a study reported by the US Huntington Disease Genetic Testing Group from the Hennepin County Medical Center, Minneapolis, MN.